Thermophysical Properties of Alkanone + Aromatic Amine Mixtures at Varying Temperatures - Prabhune, Aditi; Natekar, Amrita; Dey, Ranjan (Frontiers in Chemistry, 2022)
In the present investigation, an attempt has been made to evaluate internal pressure (P_i), energy (〖∆E〗_vap) and enthalpy of vapourization (〖∆H〗_vap) along with excess entropy 〖(S〗^E) and excess isothermal compressibility 〖(β〗_T^E)for binary solutions of alkanones (2-Propanone, 2-Butanone, 2-Heptanone) and aromatic amines (Aniline, N-Methylaniline, Pyridine) at 293.15, 298.15 and 303.15 K. Cohesive energy density (CED) and Solubility parameter (δ) are studied to understand strength of molecular interactions. Coefficient of thermal expansion (α) and isothermal compressibility 〖(β〗_T) have also been investigated using empirical equations and have been employed to understand the molecular interactions. All the evaluated properties have been used to understand the nature and extent of intermolecular interactions taking place. The observed trends in the properties and their variations have been discussed in terms of varying chain length of alkyl group and hydrogen bonding capability of the components. The findings show that the extent of interactions follows an order Aniline > NMA > Pyridine, keeping the alkanone constant at all the temperatures under study.